The distribution of agglutinins and lytic activity against Trypanosoma rangeli and erythrocytes in Rhodnius prolixus and Triatoma infestans tissue extracts and haemolymph - Gregório, Elisa A. [UNESP]; Ratcliffe, Norman A. (Instituto Oswaldo Cruz, Ministério da Saúde, 1991)
Haemolymph, heads, salivary glands, crops, midguts, hindguts, and Malpighian tubules from Rhodnius prolixus and Triatoma infestans were extracted in phosphate or Tris buffer saline with calcium, and tested for agglutination and lytic activities by microtitration against both vertebrateerythrocytes and cultured epimatigote forms of Trypanosoma rangeli. Haemagglutination activity against rabbit erythrocytes was found in the crop, midgut and hindgut extracts of T. infestans but only in the haemolymph of R. prolixus. Higher titres of parasite agglutinins were found in R. prolixus haemolymph than T. infestans, whilst the converse occurred for the tissue extracts. In addition, the extracts of T. infestans salivary glands, but not those of R. prolixus, showed a trypanolytic activity that was heat-inactivated and was not abolished by pre-incubation with any of the sugars or glycoproteins tested. T. infestans, which is refractory to infection by T. rangeli, thus appears to contain a much wider distribution of agglutinating and trypanolytic factors in its tissues than the more susceptible species, R. prolixus
Keywords: haemagglutinin; Rhodnius prolixus; Triatoma infestans; haemolymph; trypanolytic factor; Trypanosoma rangeli